An Update on the Pathogenic Role of Macrophages in Adult-Onset Still’s Disease and Its Implication in Clinical Manifestations and Novel Therapeutics - Po-Ku Chen; Der-Yuan Chen (Journal of Immunology Research)
Increasing evidence indicates a pivotal role of macrophages in innate immunity, which contributes to the pathogenesis of adult-onset Still’s disease (AOSD). Despite the available reviews that summarized the pathogenic role of proinflammatory cytokines in AOSD, a systematic approach focusing on the crucial role of macrophages in this disease is still lacking. This review summarizes the updated functions of macrophages in AOSD and their implication in clinical manifestations and therapeutics. We searched the MEDLINE database using the PubMed interface and reviewed the English-language literature as of 31 March 2021, from 1971 to 2021. We focus on the existing evidence on the pathogenic role of macrophages in AOSD and its implication in clinical characteristics and novel therapeutics. AOSD is an autoinflammatory disease mainly driven by the innate immune response. Among the innate immune responses, macrophage activation is a hallmark of AOSD pathogenesis. The pattern recognition receptors (PRRs) on macrophages recognize pathogen-associated molecular patterns and damage-associated molecular patterns and subsequently cause overproduction of proinflammatory cytokines and recruit adaptive immunity. Some biomarkers, such as ferritin and gasdermin D, reflecting macrophage activation were elevated and correlated with AOSD activity. Given that macrophage activation with the overproduction of proinflammatory cytokines plays a pathogenic role in AOSD, these inflammatory mediators would be the therapeutic targets. Accordingly, the inhibitors to interleukin- (IL-) 1, IL-6, and IL-18 have been shown to be effective in AOSD treatment. Gaining insights into the pathogenic role of macrophages in AOSD can aid in identifying disease biomarkers and therapeutic agents for this disease.